Pemanfaatan Campuran Kulit Kayu Nangka Dan Kapur Sebagai Pengganti Sabun Untuk Menghambat Fermentasi Nira Kelapa - Prio Asmoro, Seto, Triastuti Rahayu, S.Si., M.Si (2015)
A mixture of jackfruit and lime bark is an alternative to soap as an inhibitor of fermentation of coconut sap more natural and decent existence sugar in processed products. The purpose of this study to determine whether a mixture of jackfruit and lime bark can replace soap to inhibit fermentation of coconut sap. This research method using a completely randomized design (CRD) with two factors, one is the heavy mixture of bark jackfruit and lime (B1 = 3 grams, B2 = 4 grams) and a factor of 2 which is the ratio of bark jackfruit: lime (P0 = 0% : 0%, P1 = 50%: 50%, P2 = 65%: 35%, P3 = 35%: 65%) with 8 treatments. Results showed that the lowest total acid (1.706%) and highest degree of acidity (pH = 4.2) contained in coconut sap treatment with P1B2 (bark jackfruit 50% and 50% by weight of lime formulations of 4 grams). Based on quantitative research and acid total acidity, a mixture of jackfruit and lime bark can not replace soap as an inhibitor of fermentation of coconut sap. Keyword : coconut sap, fermentation, jackfruit wood, limestone, total acid.